Avaliação do custo total como ferramenta para a análise de investimentos ambientais - Gabriela Liliana Egea (2008)
In the last few decades the State and the consumers have showed great concerns aboutpreserving the environment, for which they ve been playing an orientated role on the businessdecisions the companies are supposed to take. While the State plays this role with itsregulations, the consumers make it by means of their guided demand for green products .Consequently, the companies are obliged to rethink their products and productive processescreating the necessity of accomplishing environmental investments. But in spite of the broadliterature that aims the profitability of such investments, the reality shows that they areneglected by the decisions makers, having as one of the causes the lack of a tool that enablesthem to catch the environment costs and economies particularities. This work proposal is toshow that the total Costs Assessment methodology is a viable tool to fulfill this deficiency ofthe traditional investments analysis, making possible that pollution prevention projects can betaken into consideration equally with other projects of investments, competing fairly for thesame limited financial resources.